The effects of tasks on language-related episodes (LREs) during focus-on-form instruction - Ismail, Lilliati; Abd. Samad, Arshad (IDP Education, 2010)
This paper discusses the effectiveness of using two task-types, dictogloss and opinion-gap tasks, in focus-on-form lessons to elicit language-related episodes (LREs) and produce modified output. The participants were 40 Form 6 students in a Malaysian secondary school in two intact classes. One group was taught using opinion-gap tasks and the other using dictogloss tasks. Results show that almost double the number of LREs was elicited in the dictogloss group compared to the opinion-gap group. However, more than 50% of the LREs in both groups were unresolved or wrongly resolved. These results imply the need to train learners to notice linguistic errors and engage in negotiations of form and meaning and could also indicate the need for teacher feedback on language use, perhaps during pre-task and post-task activities. The types of linguistic errors learners focused on might be an indication of learner developmental readiness which could influence task and text selection.